Effectiveness of administration of bronchodilator by spacers, home-made spacers and nebulizers in patients with chronic obstructive pulmonary disease - Lesmana, Andrean; Tarigan, Amira Permatasari; Syarani, Fajrinur (International Journal of Research in Medical Sciences, 2019)
Background: In chronic obstructive pulmonary disease (COPD), bronchodilator therapy using dry powder inhaler (DPI) or a measured dose inhaler (MDI) is more convenient at a lower cost than nebulizer therapy. Mistakes in the use of MDI often occur due to lack of coordination but with the addition of spacers, drawbacks in the use of this MDI can be overcome so that it does not require coordination. Commercial spacers are relatively expensive and not available anywhere while home-made spacers made from bottles of mineral water are very cheap and can be made alone. Study aimed to evaluate the effectiveness of each device, namely a spacer, a home-made spacer and nebulizer. Methods: This study is an experimental study of 62 COPD patients who received bronchodilators using spacers, home-made spacers, and nebulizers. Spirometry is performed for each sample before and after bronchodilator administration to assess FEV1, KVP and changes in VAS dyspnea. The difference in the effectiveness of bronchodilators for various devices in COPD patients was statistically analyzed using the ANOVA test. Results: There were significant differences in the values of VEP1, KVP and VAS dyspnoea after bronchodilator administration through the spacer, home-made spacer and nebulizer (p<0.001), (p=0.002), (p<0.001). The increase in% VEP1 with a nebulizer device was higher than that of a spacer (p=0.001) and the increase in% VEP1 with the nebulizer device was also significantly significant compared to home-made spacer (p<0.001). The increase in% KVP with the nebulizer device was higher than that of home-made spacer (p<0.001), as well as between spacers and home-made spacers and this was significant (p=0.038). The decrease in VAS dyspnoea in patients using nebulizer device than the spacer (p<0.001). Decreasing VAS dyspnoea with nebulizer devices is higher compared to home-made spacers, also gives significant results (p<0.001). There were no differences in the decrease in VAS dyspnoea between spacers and home-made spacers. Conclusions: The administration of bronchodilators by use of three devices (spacers, home-made spacers and nebulizers) can significantly increase the values of FEV1, KVP and VAS dyspnoea. On the use of spacers and home-made spacers, the increase of pulmonary physiological values is not significantly different.